1997
DOI: 10.1038/sj.onc.1201252
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 proteins are transported to the nucleus in the absence of serum and splice variants BRCA1a, BRCA1b are tyrosine phosphoproteins that associate with E2F, cyclins and cyclin dependent kinases

Abstract: BRCA1, a familial breast and ovarian cancer susceptibility gene encodes nuclear phosphoproteins that function as tumor suppressors in human breast cancer cells. Previously, we have shown that overexpression of a BRCA1 splice variant BRCA1a accelerates apoptosis in human breast cancer cells. In an attempt to determine whether the subcellular localization of BRCA1 is cell cycle regulated, we have studied the subcellular distribution of BRCA1 in asynchronous and growth arrested normal, breast and ovarian cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
146
1
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(153 citation statements)
references
References 23 publications
5
146
1
1
Order By: Relevance
“…Previous studies have shown that the first 76 aa of BRCA1 interact with multiple cell-cycle factors including cdc2, cdk2, cdk4, cyclin B, cyclin D, cyclin A and E2F-4 (Wang et al, 1997). Our data demonstrates that the principal areas of interaction are the N terminus (aa 1-500) and aa 504-802.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Previous studies have shown that the first 76 aa of BRCA1 interact with multiple cell-cycle factors including cdc2, cdk2, cdk4, cyclin B, cyclin D, cyclin A and E2F-4 (Wang et al, 1997). Our data demonstrates that the principal areas of interaction are the N terminus (aa 1-500) and aa 504-802.…”
Section: Discussionsupporting
confidence: 56%
“…Likewise, various cyclin/cdk complexes, including cyclin D, have been shown to phosphorylate BRCA1 (Wang et al, 1997;Ruffner et al, 1999); however, the consequence of cyclin D1/cdk phosphorylation on BRCA1 has not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Lyn is a potential regulator of Brca1, acting via Akt Altiok et al, 1999;Shivakrupa and Linnekin, 2005). Brca1 is itself a potential regulator of Lyn, acting via CDC2 (Pathan et al, 1996;Wang et al, 1997). Furthermore, the downstream transducer of c-Kit signalling, Stat5a, is negatively regulated by Brca1 (Brizzi et al, 1999;Vidarsson et al, 2002), while Stat1 and Jak2 are positively regulated by both Brca1 and c-Kit Chin et al, 1998;Ouchi et al, 2000;Gao et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The morphology of the DElk-1 transfectants were similar to that of the parental cells. We analysed the expression of Elk-1 and DElk-1 proteins in Elk-1 and DElk-1 transfectants by indirect immuno¯uorescence analysis, immunoperoxidase staining (Figure 1) and Western blot analysis (Figure 2) using Elk-1 polyclonal antibody as described previously Wang et al, 1997). The nuclear and cytoplasmic staining was brighter and stronger in both Elk-1 and DElk-1 transfected cells compared to parental Rat-1 fibroblast cells suggesting higher levels of expression of Elk-1 and DElk-1 proteins in transfected cells ( Figure 1).…”
mentioning
confidence: 99%